2009
DOI: 10.2174/1874609810902010043
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial Memory in Healthy Elderly, AD and MCI: A Review

Abstract: In the literature it is commonly reported that several spatial abilities decline with normal aging, even though such a decline is not uniform. So far, it is not yet clear which spatial components present a normal age-related decline, which ones are preserved and at what point the deficit is so severe to represent an index of mild cognitive impairment (MCI) or a symptom of potential degenerative progression as in the early-stage Alzheimer's disease (AD). In particular, AD (from early onset) is characterised by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
142
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 154 publications
(180 reference statements)
8
142
1
1
Order By: Relevance
“…Results revealed a deficit of the allocentric component in AD and amnesic-MCI patients (see also Dawson, Anderson, Uc, Dastrup, & Rizzo, 2009;Laczó et al, 2012). This suggests that a severe drop in the allocentric capacity could be a prodromic sign of a neurodegenerative disease (Hort et al, 2007;Iachini et al, 2009a).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Results revealed a deficit of the allocentric component in AD and amnesic-MCI patients (see also Dawson, Anderson, Uc, Dastrup, & Rizzo, 2009;Laczó et al, 2012). This suggests that a severe drop in the allocentric capacity could be a prodromic sign of a neurodegenerative disease (Hort et al, 2007;Iachini et al, 2009a).…”
Section: Discussionmentioning
confidence: 88%
“…Spatial memory efficiency is associated with structural and functional integrity of the spatial memory neural network (i.e., hippocampus, parahippocampal gyrus, retrosplenial, postero-cingulate cortex, parietal lobe and frontal areas) that involves the allocentric encoding (hippocampus and surrounding areas) and also executive functions (Burgess, 2008;Cabeza & Dennis, 2012;Galati et al, 2010;Iachini et al, 2009a;Moffat, 2009;Vann, Aggleton, & Maguire, 2009). Much research has documented that normal aging is characterized by reductions in the volume of the hippocampus and the frontal cortex, such as to produce allocentric (e.g., Rodgers et al, 2012) and egocentric (e.g., Head & Isom, 2010;Wilkniss et al, 1997) difficulties and a general decline in executive and attentional functions (Iachini et al, 2009a;Lithfous et al, 2013;Salthouse, 1996). Executive functions are necessary to acquire, combine and select spatial strategies, to plan and monitor behavioral motor responses according to environmental requirements (Lithfous et al, 2013;Vasilyeva & Lourenco, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed results have been found for age effects when learning locations from maps and small-scale arrays not requiring physical movement to explore. While some have found clear evidence of spatial decline (Iachini et al, 2009; Kirasic, 2000; Moffat & Resnick, 2002), others have shown preservation when memory prompts are present (Yamamoto & DeGirolamo, 2015) or a mix of preservation and decline depending on alignment of perspective (Borella, Meneghetti, Muffato, & De Beni, 2015). The encoding and retention of spatial layouts by older adults clearly merits further examination, as in the present studies.…”
Section: Introductionmentioning
confidence: 99%
“…Having the condition is widely considered to be a highly predictive risk factor for the development of Alzheimer's Disease (AD; Morris et al, 2001;Petersen, 2004) and there is therefore diverse research into identifying aMCI patients, understanding their cognitive impairments, and predicting later conversion to dementia (Blennow, Hampel, Weiner, & Zetterberg, 2010;Prvulovic, Bokde, Faltraco, & Hampel, 2011;Sperling, 2011;Wolk & Detre, 2012). There has been a recent emphasis on investigating spatial navigation in normal and pathological aging (Gazova et al, 2012;Iachini, Iavarone, Senese, Ruotolo, & Ruggiero, 2009;Lithfous, Dufour, & Després, 2013;Moffat, 2009). Spatial navigation impairments occur early in the progress of AD, where patients can be disoriented even in familiar surroundings (Henderson, Mack, & Williams, 1989;Monacelli, Cushman, Kavcic, & Duffy, 2003).…”
mentioning
confidence: 99%